Familiarity, perception, and reasons for electronic‑cigarette experimentation among the general public in Malaysia: Preliminary insight - Elkalmi, Ramadan Mohamed Mahmod; Bhagavathul, Akshaya Srikanth; Ya’u, Adamu; Al‑Dubai, Sami Abdo Radman; Elsayed, Tarek Mohamed Ali; Ahmad, Akram; Yusef Mohamed, Wael Mohamad (Medknow Publications and Media Pvt. Ltd, 2016)
Objectives: The objectives of this study were to assess the general public views and familiarity toward electronic cigarette (e‑cigarette) in Kuantan, Malaysia. Methodology: A total of 277 Kuantan people were involved in this study. The questionnaire was distributed at random in shops, businesses, and public places in Kuantan. Statistical analysis was performed using SPSS (version 17.0). Results: From 400 participants, a total number of 277 (160, 57.7% men and 117, 42.4% women) respondents completed the questionnaire. The mean age was 26.89 ± 9.8 years old. The majority of the study participants were male (57.7%), Malay (83.8%), Muslims (83.8%), singles (69%), and employed (75.8%), with about 83 (29.9%) of the respondents were smokers. The prevalence of e‑cigarettes smokers was found to be only 1.4% (n = 4). About one‑third of the respondents (n = 72, 26%) have tried e‑cigarette before. Job status was significantly associated with smoking e‑cigarette among the population (P = 0.02). Main factors for a person to start e‑cigarette smoking were curiosity (37.5%) and cheaper price (40.8%). Majority of respondents agreed that e‑cigarette would not affect health as normal cigarette, and that variety of flavors contribute to better enjoyment (51.6% and 66.7%, respectively). Conclusion: The results of the current study demonstrate that the prevalence of e‑cigarettes smoking and its popularity, familiarity, and knowledge are still insufficient among Kuantan population. Further studies should be done to tackle this problem before it getting worse.